DIPG-38. ID1 EXPRESSION CORRELATES WITH H3F3A K27M MUTATION AND EXTRA-PONTINE INVASION IN DIPG. Issue 2 (22nd June 2018) - Stallard, Stefanie; Siddaway, Robert; Miklja, Zachary; Mullan, Brendan; Garcia, Taylor; Zamler, Daniel; Kasaian, Katayoon; Cao, Xuhong; Anderson, Bailey; Hervey-Jumper, Shawn; Castro, Maria G; Lowenstein, Pedro R; et al.
Abstract: ID1 regulates transcription by interacting with bHLH transcription factors and previous work has shown that over-expression of the recurrent DIPG H3F3A K27M and ACVR1 mutations in cultured astrocytes lead to an increase in ID1 expression; this has not been validated in human DIPG. DNA (exome)/RNA sequencing of 34 DIPGs and 17 normal samples (SickKids) revealed that ID1 expression was significantly increased in tumor as compared to normal (p=0.001). ID1 expression was significantly higher in H3F3A K27M-mutated tumors as compared to normal (p=0.003), but not in ACVR1 -mutated tumors. This was confirmed in an analysis of pediatric high-grade gliomas (PedcBioPortal) where ID1 expression was increased in H3F3A K27M-mutated tumors as compared to H3 wildtype (p=0.0055, n=189), but not in ACVR1 -mutated tumors as compared to ACVR1 wildtype (p=0.1178, n=114). In an additional patient with DIPG at autopsy, multi-focal sequencing revealed clonal mutations in HIST1H3B K27M and ACVR1 and ID1 expression correlated with tumor size and cerebellar invasion. We identified several genes whose expression in pediatric HGG correlated with that of ID1 and which have been implicated in invasion and/or metastasis in various solid tumors. ChipSeq revealed reduced K27 me3 and elevated K27 acetylation at the ID1 locus in multiple K27M-mutant DIPG cell lines, pointing to an epigenetic control of this phenotype in H3F3A K27M-mutated DIPGs. Based on these data, we propose that epigenetically controlled upregulation of ID1 promotes DIPG invasion in H3F3A K27M-mutated DIPG and represents an optimal therapeutic target.